Yours Presently : The Selected Letters of John Wieners - Wieners, John, 1934-2002 (Book collections on Project MUSE., 2020)
The letters collected in this volume are greatly enhanced by Eileen Myles's preface and Stewart's thorough introduction, notes, and brief bios of the poets, writers, artists, and editors with whom Wieners corresponded.